2012
DOI: 10.1115/1.4004840
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Combustion Resonance Using an Ion Current Sensor in Diesel Engines

Abstract: This paper discusses the use of an ion current sensor to detect combustion resonance in a heavy duty direct injection diesel engine. A modified glow plug is used to measure the ion current in addition to its main function in warming up the combustion chamber. A comparison is made between the combustion resonance determined from the signals of an ion current sensor, a cylinder pressure transducer, and an engine vibration sensor. Experiments are conducted on a four cylinder, turbocharged 4.5 liter diesel engine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The authors of [34] proposed a system for the diagnosis of damage to combustion engines using wavelet packet transform (WPT) and artificial neural network (ANN) techniques. Article [5] discusses the application of the ionic current sensor for detecting combustion resonance in a direct injection diesel engine. A modified glow plug is used to measure ionic current in addition to its main function of heating the combustion chamber.…”
Section: Engine Valve Clearance Diagnostics Based On Vibration Signals and Machine Learning Methodsmentioning
confidence: 99%
“…The authors of [34] proposed a system for the diagnosis of damage to combustion engines using wavelet packet transform (WPT) and artificial neural network (ANN) techniques. Article [5] discusses the application of the ionic current sensor for detecting combustion resonance in a direct injection diesel engine. A modified glow plug is used to measure ionic current in addition to its main function of heating the combustion chamber.…”
Section: Engine Valve Clearance Diagnostics Based On Vibration Signals and Machine Learning Methodsmentioning
confidence: 99%
“…There are many experimental studies on the identification of high-frequency pressure oscillation of the engine by signal processing methods [25][26][27][28][29]. Saeed Siavoshani [25] defined a Wiener filter that characterizes the fluctuation of the cylinder pressure and multiplies the Wiener filter by the combustion pressure signal to obtain combustion contribution of the vibration of the engine block.…”
Section: Introductionmentioning
confidence: 99%
“…Saeed Siavoshani [25] defined a Wiener filter that characterizes the fluctuation of the cylinder pressure and multiplies the Wiener filter by the combustion pressure signal to obtain combustion contribution of the vibration of the engine block. Badawy et al [26] studied the effect of injection pressure and exhaust-gas recirculation (EGR) on combustion resonance by inserting an ion current sensor. Albarbar et al [27] investigated the air-borne acoustic signal in the vicinity of injector head combined with independent component analysis (ICA) to decompose the acoustic signals, and found that the recovered energy level of high frequency band 9-15 kHz was affected by the injector pressure setting.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the task of developing highly sensitive and accurate methods for diagnosing the gas distribution mechanism is very relevant [19,20]. This will allow us to determine the emerging failures at the initial stages [21][22][23][24]. Thus, according to some data, more than 30 % of engine failures fall at the GDM (Figure 1).…”
Section: Introductionmentioning
confidence: 99%